Analisis Produksi dan Risiko Produksi Usahatani Padi pada Daerah Irigasi dan Non Irigasi di Kabupaten Banjar - Muzdalifah Muzdalifah (Universitas Lambung Mangkurat, 2011)
This study is aimed to know the determinated of production and it risk of paddy farming in the irrigation and non irrigation areas with the determinants of those variables. The proposed hypotheses are (1) the factors influencing the production and it risk production are crop area, seed, fertilizer, labor, superior seed and irrigation areas, (2) the risk of production of irrigated paddy farming are lower than the one of the non irrigated paddy farming. The data used are primary and secondary data. The primary data were obtained by doing some interviews with 80 randomly choosed rice farmers at two subdistricts of Kabupaten Banjar. The characteristics of farmers and the use of the production infrastructures were also observed. The analysis methodology used are multiple regression with Ordinary Least Squares (OLS) and the Coefficient of Variation (CV). The results show that crop area, seed, urea, KCl and ponska influence to the production. KCl, ponska, pesticide, labor and irrigation influencing the production risk. The risk of production at the irrigated areas is lower than the risk at the non irrigated areas wtih CV of them are 0.77 and 0.83, respectively.